An Introduction to Object-Oriented Programming With Java - Wu Thomas C. (McGraw -Hill, 2005)
An Introduction to Object-Oriented Programming with Java provides an accessible and technically thorough introduction to the basics of programming using java. The fourth edition continues to take a truly object-oriented approach. Objects are used early so that students think in objects right from the beginning.